Challenges Faced by Post-Treatment Childhood Cancer Patients and Families; The Children's Hospital, Lahore Experience - Kashif, Muhammad; Faizan, Mahwish; Zafar, Huma; Saeed, Maria; Shahid, Fatima (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess challenges faced by post-treatment childhood cancer patients and families in a developing country.Study Design: cross-sectional study.Place and Duration of Study: The Children's Hospital and the Institute of Child Health Lahore, from Jul to Dec 2020.Methodology: 105 children and their parents were enrolled on OPD of the Department of Paediatric Hematology and Oncology. The parents were questioned regarding the duration of follow-up after treatment and the challenges they faced during this interval in association with socioeconomic dynamics, education and awareness of parents, travelling distance from the hospital, behavioural changes in children, toxicities/disabilities due to treatment, effect on other siblings, and various factors.Results: In this study, the mean age of children was 9.40 ± 2.90 years. There were 55 (52.4%) males while 50 (47.6%) females. There were 35 (33.3%) children who had acute lymphocytic leukaemia, while 15 (14.3%) with Hodgkin Lymphoma, 12 (11.4%) with Wilms tumour, 10 (9.5%) with Non-Hodgkin Lymphoma, 9 (8.6%) with germ cell tumour and 7 (6.7%) with acute myeloid leukaemia. Mostly, 89 (84.8%) children received chemotherapy, while 12 (11.4%) children received chemotherapy as well as radiotherapy, and 4 (3.8%) children underwent surgery along with other treatments. The distance from the hospital was more than 50 km in >90 cases. Moreover, 42 (40.0%) children were found malnourished. Out of 105, 71 parents reported that the treatment affected their jobs, while 52 (49.5%) parents had to change their residence. The family's economic status wasaffected in 77 (73.3%) cases because of the treatment...........